E-Dakwah Islam Digest Republika.Co.Id. di Indonesia - Ujang Saepullah; Khoiruddin Muchtar (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
The research aims to analyze and understand the vision and mission of E-Da'wah, sources of content that are used as a reference, selected preaching content, and language style displayed in Islam Digest Republika.co.id. The research uses a case study method, a qualitative approach, using new media theory, and information dissemination theory. The research results show that the vision carried out by Republika.co.id's Digest Islamic Digest is modern, moderate, Muslim, nationality, and populist, with a mission as an advanced, intelligent, and civilized new online media. While the sources of the Islamic Digest news are taken from the primary causes of the teachings of Islam al-Quran Hadith and the works of classical and contemporary scholars. Likewise, the selected content around aqidah, sharia, Sufism, history, and others, by displaying popular language styles that are interesting and easy to read.Penelitian bertujuan untuk menganalisis dan memahami visi misi E-Dakwah, sumber-sumber konten yang dijadikan rujukan, konten-konten dakwah yang dipilih dan gaya bahasa yang ditampilkan dalam Islam Digest Republika.co.id. Penelitian menggunakan metode studi kasus, pendekatan kualitatif, dengan menggunakan teori media baru dan teori penyebaran informasi. Hasil Penelitian menunjukan bahwa visi yang diemban E-Dakwah Islam Digest Republika.co.id adalah modern, moderat, muslim, kebangsaan, dan kerakyatan, dengan misi sebagai media online masyarakat baru yang maju, cerdas, dan beradab. Sedangkan sumber-sumber berita Islam Digest diambil dari sumber pokok ajaran Islam al-Quran Hadits dan karya-karya ulama klasik dan kontemporer. Demikian pula konten-konten yang dipilih sekitar aqidah, syariah, akhlak tasawuf, sejarah, dan yang lainnya, dengan menampilkan gaya bahasa populer yang menarik dan enak dibaca.